2015
DOI: 10.1097/psy.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Weight Loss

Abstract: Significant weight loss was documented among participants in mindfulness interventions for 13 of the 19 studies identified for review. However, studies do not clarify the degree to which changes in mindfulness are a mechanism responsible for weight loss in mindfulness interventions. Methodological weaknesses and variability across studies limit the strength of the evidence. Further research is needed to document and evaluate the psychological, behavioral, and biological mechanisms involved in the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 44 publications
2
132
1
5
Order By: Relevance
“…These mindfulness programmes contained core elements of mindfulness including meditation, awareness and being present. A recent review on the effectiveness of mindfulness in achieving weight loss found that the majority of studies did result in weight loss but the extent to which mindfulness could be attributed to the effect was not apparent (22) . This study also noted the wide variation in interventions and methodological weaknesses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mindfulness programmes contained core elements of mindfulness including meditation, awareness and being present. A recent review on the effectiveness of mindfulness in achieving weight loss found that the majority of studies did result in weight loss but the extent to which mindfulness could be attributed to the effect was not apparent (22) . This study also noted the wide variation in interventions and methodological weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mindfulness in weight management was less apparent (20,21) . The high level of heterogeneity between studies (20) and methodological weakness of many studies (22) were highlighted. Mindfulness is a key component of interventions based on dialectical behaviour therapy and Acceptance and Commitment Therapy (ACT), which are both third-wave therapies to promote awareness, acceptance and distress tolerance (19) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, attention to the present moment should support the differentiation between physiological hunger signals and other internal or external stimuli for eating, such as negative emotions or food availability (Brown et al, 2007; Olson & Emery, 2015). Nearly all existing studies characterizing the cross-sectional relationship of dispositional mindfulness with disinhibited eating have been conducted in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Kristeller, 2003; J. L. Kristeller & Wolever, 2011), however not all studies demonstrate weight loss (K. L. Olson & Emery, 2015).…”
Section: Introductionmentioning
confidence: 99%